Porcine deltacoronavirus nsp15 antagonizes interferon-β production independently of its endoribonuclease activity - Liu, Xiaorong (Mol Immunol, 2019)
Porcine deltacoronavirus (PDCoV) is an emerging swine coronavirus causing diarrhea and intestinal damage in nursing piglets. Previous work showed that PDCoV infection inhibits type I interferon (IFN) production. To further identify and characterize the PDCoV-encoded IFN antagonists will broaden our understanding of its pathogenesis. Nonstructural protein 15 (nsp15) encodes an endoribonuclease that is highly conserved among vertebrate nidoviruses (coronaviruses and arteriviruses) and plays a critical role in viral replication and transcription. Here, we found that PDCoV nsp15 significantly inhibits Sendai virus (SEV)-induced IFN-β production. PDCoV nsp15 disrupts the phosphorylation and nuclear translocation of NF-κB p65 subunit, but not antagonizes the activation of transcription factor IRF3. Interestingly, site-directed mutagenesis found that PDCoV nsp15 mutants (H129A, H234A, K269A) lacking endoribonuclease activity also suppress SEV-induced IFN-β production and NF-κB activation, suggesting that the endoribonuclease activity is not required for its ability to antagonize IFN-β production. Taken together, our results demonstrate that PDCoV nsp15 is an IFN antagonist and it inhibits interferon-β production via an endoribonuclease activity-independent mechanism.